Durability of porous glasses - Rodríguez Valdivieso, Christian Raúl (2021)
The investigations of this work are dedicated to the production of highly alkali resistant porous glasses, evaluating the effect of adding ZrO2 to the sodium borosilicate Vycortype glass. The additions were made with the purpose of improving the ability of the silica porous structure to withstand alkaline solutions. Base glasses (BG) with 0 mol% ZrO2 (Zr0), 3 mol% ZrO2 (Zr3) and 6 mol% ZrO2 (Zr6) were produced by the conventional melting and quenching method. The vitreous structure of the BG was confirmed by XRD. Further characterization tests such as density, ATR and DSC were performed as well. To induce spinodal phase separation and create a two-phase matrix (an insoluble silica rich phase and a soluble sodium-borate phase), BG were heat treated at different temperatures from 560 °C to 700 °C for 12 hours. Scanning electron microscopy (SEM) confirmed the expected interconnected sponge-like morphology. Pore sizes were calculated according to the DIN EN ISO 13383 norm. There is a well-defined tendency of pore size growth with increasing heat treatment temperature and time for 0 mol% ZrO2 and 3 mol% ZrO2 glasses. SEM images also show a decrease in pore size when ZrO2 is added to the glass. The 6 mol% ZrO2 glass did not show spinodal phase separation. Based on the pore size results, a heat treatment temperature of 680 °C was chosen for the following tests. To obtain a porous sample, the soluble sodium-borate phase needs to be leached with HCl solution. For this, leaching temperature and the HCl solution were varied, as well as the subsequent drying process.The best leaching results were obtained with a solution of 1 M HCl + 70 % Ethanol (ratio 9:1) at room temperature for two days and 2 M HCl + 70 % Ethanol (ratio 9:1) at 70 °C for seven days, for Zr0 and Zr3, respectively. To study the durability of porous glasses, alkali resistance tests against 0.1 M NaOH were carried out. It was shown that the alkali stability of Zr0 glass is very low (mass loss of about 20 % in 22 hours). However, when 3 mol% ZrO2 is added to the glass the weight loss percentage is reduced significantly (mass loss of about 4 % in 22 hours). It was found that the presence of zirconia in the silica rich porous structure improves the stability against alkali dramatically. A big problem is the leaching of the phase separated glasses, which very often resulted in breaking of the samples.